2012
DOI: 10.1111/j.1467-8535.2011.01269.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effectiveness of a 3‐D instructional game on improving mathematics achievement and motivation of middle school students

Abstract: revolve around statistical methods, specifically, resampling methods, propensity score analysis, research design, measurement and the applications of statistical methods in educational research and behavioral sciences. Wei Pan, PhD, is an associate professor of Quantitative Research Methodology in the College of Education, Criminal Justice, and Human Services at the University of Cincinnati. His current research interests are causal inference, propensity score analysis, resampling, multilevel modeling, structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 34 publications
2
50
1
3
Order By: Relevance
“…Devlin therefore suggests that using appropriate video games in mathematics education could be extremely valuable in solving problems related to student motivation and achievement. In fact, this claim has been explored and empirically supported by past research concerning specific video games (see for instance [2]). …”
Section: Introductionmentioning
confidence: 66%
“…Devlin therefore suggests that using appropriate video games in mathematics education could be extremely valuable in solving problems related to student motivation and achievement. In fact, this claim has been explored and empirically supported by past research concerning specific video games (see for instance [2]). …”
Section: Introductionmentioning
confidence: 66%
“…The use of Valsiner's (1997) theory of human development to conceptualise the diffusion of innovations in an educational context has shown that change is slower in the traditional setting of a school which is characterised by complex political relations and significant pressures on teachers and school leaders to understand and interpret change. A number of empirical studies which demonstrate educational benefits of digital games have recently emerged (Bai et al 2012;Hess and Gunter 2013;Ke 2008;Miller and Robertson 2011). These studies encourage educators to innovate with confidence.…”
Section: Discussionmentioning
confidence: 98%
“…Others (Barab et al 2005) see exciting possibilities for digital games to increase participation in education and promote active citizenship. A number of recent empirical studies (e.g., Bai et al 2012;Hess and Gunter 2013;Ke 2008;Miller and Robertson 2011) discern significant learning gains through the use of digital games. Thomas and Brown (2011) argue a persuasive case for using digital games for people to better connect with each other and hone collaborative skills.…”
Section: Introductionmentioning
confidence: 98%
“…En cambio, en este estudio no se observa un aumento en la motivación de los alumnos al utilizar este tipo de videojuegos. En un trabajo posterior del mismo equipo de investigación, H. Bai et al (2012) utilizan otro videojuego de la compañía DimensionU (Tabula Digita, en este caso) en el que se han implemenado mejoras en las dinámicas de juego, como es el juego cooperativo. Los resultados en este segundo estudio van en la línea de corroborar la mejora en los resultados de conocimiento matemático sobreálgebra, a la vez que muestran un evidente progreso en los aspectos motivacionales hacia la propuesta de aprendizaje que consideran fundados en los cambios a nivel de diseño en el videojuego.…”
Section: Videojuegos Para Incentivar Mejoras En El Rendimiento Matemáunclassified